The Social and Cultural Capital Exploration Keeping Personal Hygiene in Children - ., Marniati; ., Yarmaliza (International Journal of Engineering and Technology, 2018)
Knowledge of parents is very important in the formation of the underlying behaviors that support or do not support the child's oral hygiene. The number of children aged 9 to 12 years with impaired oral around Puskesmas SUAK Ribee are as many as 230 people in 2014 and 183 in 2015 from January to September 18, 2015. The purpose of research is to determine the effect of knowledge and the mother's attitude to Dentistry and Oral on elementary School Students 19 SUAK Ribee West Aceh District. This research is an analytic with cross-sectional design. The research was conducted in SD Negeri 19 SUAK Ribee West Aceh district on 11 to 21 November 2015 with a population sample of 178 respondents and 64 people, with univariate and bivariate analysis using chi-square test. The results showed that the mother's knowledge and attitudes significantly affect children's personal hygiene (P.Value <0.05).Â Â